2008
DOI: 10.1186/bf03352769
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional velocity structure in the source region of the Noto Hanto Earthquake in 2007 imaged by a dense seismic observation

Abstract: The velocity structure and accurate aftershock distributions of the Noto Hanto Earthquake in 2007 (thrust type) are elucidated by inverting the arrival times from 917 aftershocks using double-difference tomography. P-wave velocity (V p ) of the hanging wall in the southeast appears to be higher than that of the footwall in the northwest, and the high-V p body of the hanging wall has a relatively high V p /V s ratio. Conversely, the low-V p body in the footwall appears to have a low V p /V s ratio at depths gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…In our study area, it is difficult to consider the latter two possibilities as explaining the existence of the conductor because of the distance from the volcanic front. Kato et al (2008) elucidated a detailed velocity structure by using data from a dense temporal seismic network and detected a distinct low velocity anomaly near and beneath the mainshock that corresponds to the C1 block. This correlation between the seismic tomography and magnetotelluric images may suggest that the conductor represents a fluid-filled zone.…”
Section: Discussionmentioning
confidence: 99%
“…In our study area, it is difficult to consider the latter two possibilities as explaining the existence of the conductor because of the distance from the volcanic front. Kato et al (2008) elucidated a detailed velocity structure by using data from a dense temporal seismic network and detected a distinct low velocity anomaly near and beneath the mainshock that corresponds to the C1 block. This correlation between the seismic tomography and magnetotelluric images may suggest that the conductor represents a fluid-filled zone.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of earlier studies of crustal structures in the source region of recent shallow large earthquakes along the Japan Sea coast, it has been suggested that complex structures associated with crustal stretching and uplift during the opening of the Japan Sea have the potential to nucleate mainshocks and trigger sequences of aftershocks (e.g., Kato et al, 2006Kato et al, , 2008. It is, therefore, of critical importance to image the complex seismogenic structures surrounding the source region and clarify their relationship to the rupture process (e.g., Thurber et al, 1995;Chiarabba et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Technological advances have also allowed higher-resolution imaging of fault zones, and spatially high-density seismic observations of aftershock events after large earthquakes in Japan have enabled the identification of seismic structures along and at right angles to the strike of fault planes. Such studies have included a review of earthquakes in Japan that reported the clear imaging of the seismic structures of source faults of major earthquake events (Hasegawa et al, 2009), including the link between low-velocity zones and earthquake-related disasters (Kato et al, 2008(Kato et al, , 2011Hasegawa, 2003, 2008;Okada et al, 2007Okada et al, , 2012Zhao et al, 2004), such as the 1962Northern Miyagi, 1995Kobe, 2000Western Tottori, 2003Northern Miyagi, 2004Chuetsu, 2007Chuetsuoki, 2007Noto Hanto, and 2008 Iwate-Miyagi earthquakes. The observed low-velocity zones and/or high-Vp/Vs zones at the source areas of these intraplate earthquakes were considered to be related to the presence of crustal fluids.…”
Section: Discussionmentioning
confidence: 99%